COMPARISON OF A DNA BASED PCR APPROACH WITH CONVENTIONAL METHODS FOR THE DETECTION OF MYCOBACTERIUM TUBERCULOSIS IN MOROCCO - Fathiah Zakham; Oufae Lahlou; Mohammed Akrim; Nada Bouklata; Sanae Jaouhari; Khalid Sadki; Fouad Seghrouchni; Mohammed Elmzibri; Abdelaziz Benjouad; Moulay Mustapha Ennaji; Rajae Elaouad (Mediterranean Journal of Hematology and Infectious Diseases, 2012)
Background: Worldwide, tuberculosis (TB) is a major public health problem and the rapid diagnosis and appropriate chemotherapy become the first priority and a serious challenge to improve TB treatment. In the objective of early TB diagnosis and rapid detection of Mycobacterium tuberculosis (MTB) in the clinical specimens, the utility of the Polymerase Chain Reaction (PCR) using the Insertion Sequence 6110 (IS6110) as target was compared to conventional methods. Methods: Out of 305 patients with different clinical manifestations: suspected, new, drug relapse, drug failure and chronic cases were enrolled in this study and tested by mycobacteriological and PCR techniques for the investigation about the tubercle bacilli. Results: The results of the in house IS6110 PCR showed a good sensitivity (92, 42%) and high specificity (98%), the positive and negative predictive values were 96.4 % and 95.3 % respectively. Conclusion: This study showed clearly that the PCR testing using the IS6110 in the routine analysis is a potential tool for the rapid TB diagnosis, especially for critical cases and would be of great interest to help the clinician in the misdiagnosed critical cases by the traditional radiology.